Effect of medication on the rostrolateral prefrontal oxygenation and thalamic volume asymmetry in youths with ADHD - Kim, Hyuna; Kang, Dahyun; Jang, Yong Hun; Ahn, Ja-Hye; Won, Sojin; Lee, Hyun Ju; Kim, Johanna Inhyang (Frontiers in Integrative Neuroscience, 2025)
IntroductionSymptoms of attention-deficit/hyperactivity disorder (ADHD) are closely associated with impaired executive function. Medication is the first-line treatment for ADHD, yet its effects on brain function and structure remain unclear. To investigate medication-related brain alterations in children with ADHD, we used functional near-infrared spectroscopy, which captures cortical hemodynamic activity, and structural magnetic resonance imaging, which measures subcortical volume.MethodsWe investigated the differences in brain hemodynamic activity between 23 children with ADHD taking medication and 22 children who were not taking medication.ResultsCompared with the medicated ADHD group, the unmedicated ADHD group showed significantly reduced activation in the left rostrolateral prefrontal cortex (channel 9, p = 0.01; channel 13, p = 0.02) and dorsolateral prefrontal cortex (channel 14, p = 0.01). The unmedicated group also exhibited a negative correlation between oxygenated hemoglobin and symptom severity, whereas the medicated group showed a positive correlation. Furthermore, abnormal asymmetry of the thalamic volume was reduced in the medicated group compared to the unmedicated group.DiscussionThese findings suggest that increased prefrontal activation and reduced thalamic asymmetry may reflect medication-related improvements in inhibitory control in children with ADHD.